KAT1 is not essential for stomatal opening. - Szyroki, Alexander; Ivashikina, Natalya; Dietrich, Petra; Roelfsema, M. R. G.; Ache, Peter; Reintanz, Birgit; Deeken, Rosalia; Godde, Matthias; Felle, Hubert; Steinmeyer, Ralf; Palme, Klaus; Hedrich, Rainer (Proceedings of the National Academy of Sciences of the United States of America, 2001)
It is generally accepted that K(+) uptake into guard cells via inward-rectifying K(+) channels is required for stomatal opening. To test whether the guard cell K(+) channel KAT1 is essential for stomatal opening, a knockout mutant, KAT1En-1, was isolated from an En-1 mutagenized Arabidopsis thaliana population. Stomatal action and K(+) uptake, however, were not impaired in KAT1-deficient plants. Reverse transcription-PCR experiments with isolated guard cell protoplasts showed that in addition to KAT1, the K(+) channels AKT1, AKT2/3, AtKC1, and KAT2 were expressed in this cell type. In impalement measurements, intact guard cells exhibited inward-rectifying K(+) currents across the plasma membrane of both wild-type and KAT1En-1 plants. This study demonstrates that multiple K(+) channel transcripts exist in guard cells and that KAT1 is not essential for stomatal action.